Audiovision and Rhythm: The “Bildwelten des Wissens” in Search of the Connection between Hearing and Perceiving (KULT_online, 2015)
For the 20th issue of “Bildwelten des Wissens” Reinhart Meyer-Kalkus and Yasuhiro Sakamoto collected essays on the topic of “Image - Sound – Rhythm”. A certain focus on Stephan von Huene’s oeuvre is complemented by contributions on Magritte’s reception of Saussure’s linguistics, Eisenstein’s theory of rhythm, and Bernd Alois Zimmermann’s ‘Musiktheater’. The quest for a specific aesthetics of audiovisuality presents itself in all of its complexity. To sharpen its fundamental relevance, however, a systematic orientation toward the third of the three concepts, “rhythm”, would have been helpful.